Estados fluidos : una intersección entre el cuerpo y lo diverso (2017)
"Estados Fluidos" is a design project that gives a new look of bodies through a post-identitarian and post-gender critique which is proposed by Queer theory. Inside the heterotopical and anthropological concept of "Estados Fluidos", identities are no longer defined through a binary reading of body nor through a sex-gender-orientation administration system. Bodies will be reconstructed and shown as a diverse structure and will not be sharp as a group of conditions but instead as an amount of possibilities. From this approach, the final design is a set of graphic pieces that question the anatomical perspectives of body, a somatic atlas where bodies are able to recreate and own a particular code, and words cannot define them." -- Tomado del Formato de Documento de Grado.